2006
DOI: 10.1248/bpb.29.976
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nuclear Factor-.KAPPA.B Activation by 2',8"-Biapigenin

Abstract: Chemoprevention is considered to be one of the most promising strategies for the prevention of human cancers. It is defined as the use of either natural or synthetic compounds to block or retard the carcinogenic process, and many natural candidates including epigallocatechin, genistein and sulforaphane have been evaluated in terms of malignancy prevention. 1-3)Recently, it was suggested that chronic inflammation is associated with carcinogenesis. 4,5) Chronic inflammation leads to the induction of specific enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 30 publications
0
28
0
1
Order By: Relevance
“…Such a decrease in phosphorylated IkBa in the cytosol in response to cranberry PACs treatment could potentially decrease the ability of p65 to translocate to the nucleus. In this regard, the effects of flavonoids upon various cancer cell lines, including DU145 human prostate cancer cells, have been examined and these studies have found a decrease in both NF-kB translocation and DNA binding after treatment with this class of compounds [Woo et al, 2006;Shen et al, 2010;Yun et al, 2009]. Recently, a study has shown that PACs from cranberries can affect both the expression and activity of select MMPs in vitro and in this study, cranberry derived PACs were able to inhibit the activation of p65 in human macrophages .…”
Section: Discussionmentioning
confidence: 99%
“…Such a decrease in phosphorylated IkBa in the cytosol in response to cranberry PACs treatment could potentially decrease the ability of p65 to translocate to the nucleus. In this regard, the effects of flavonoids upon various cancer cell lines, including DU145 human prostate cancer cells, have been examined and these studies have found a decrease in both NF-kB translocation and DNA binding after treatment with this class of compounds [Woo et al, 2006;Shen et al, 2010;Yun et al, 2009]. Recently, a study has shown that PACs from cranberries can affect both the expression and activity of select MMPs in vitro and in this study, cranberry derived PACs were able to inhibit the activation of p65 in human macrophages .…”
Section: Discussionmentioning
confidence: 99%
“…The EtOAc fraction (3.0 g) was placed on a silica gel (300 g, 4.8ϫ45 cm) column and eluted using a C-NMR data, for amentoflavone, were identical to those reported in literature. 17,23,24) The Effects of Sodium Azide (NaN 3 ) on Antifungal Activity To investigate the effects of NaN 3 on the antifungal activity of amentoflavone in C. albicans, its activity was determined either in the absence or presence of 0.002% NaN 3 . The subcultured C. albicans cells were cultured at a half of MIC in the absence or presence of 0.002% NaN 3 .…”
Section: Plant Material Fungal Strains and Growth Conditionmentioning
confidence: 99%
“…Notably, apigenin inhibits the production of IL-1␤ and TNF in mouse cells lines more effectively than resveratrol, another plant phenolic compound (22). Previous studies also showed that apigenin regulates prostaglandin and NO production in mouse cell lines through the regulation of NF-B (23). However, the molecular anti-inflammatory mechanisms of apigenin and its potential as an anti-inflammatory agent in vivo remain elusive.…”
mentioning
confidence: 99%